Potential Use of Selected Natural Anti-Microbials to Control Listeria monocytogenes in Vacuum Packed Beef Burgers and Their Impact on Quality Attributes - Angelos Papadochristopoulos; Joseph P. Kerry; Narelle Fegan; Catherine M. Burgess; Geraldine Duffy (Microorganisms)
This study assessed the potential for natural anti-microbials to control Listeria monocytogenes in vacuum packed beef burgers. Minimum inhibitory and bactericidal concentration (MIC and MBC) results for natural anti-microbials (carvacrol; essential oils of thyme, rosemary, clove and cinnamon; hop extract; cranberry extract; cranberry pomace; propolis extract; and chitosan sourced from both shrimp and mushroom) were used to select agents (n = 6) showing the most promise against L. monocytogenes. These agents, including chitosan from shrimp and mushroom (a novel source), and cranberry extract, were then tested against L. monocytogenes in vacuum packed beef burgers during chilled storage (3 ± 1 °C, 16 days). Following storage (16 d), the number of L. monocytogenes in beef burgers treated with chitosan (2.5%), regardless of source, was significantly lower (p < 0.05) (1.2 to 1.6 log10CFU g−1) than in the control samples, while smaller reductions (0.5 log10 CFU g−1; p < 0.05) were noted in samples with cranberry extract (0.625%). While chitosan had no significant impact on HunterLab colour measurements during chilled storage, cranberry extract significantly impacted the colour (p < 0.05), resulting in lower L*, a*, and b* values. Observational assessment of colour, odour and the overall quality of the raw meat on opening the pack found that beef burgers with added chitosan (both sources) were acceptable, while those with added cranberry extract received an overall quality score of approximately 5.4, which is above the acceptability threshold (5/10). Overall, the study showed the potential of chitosan to control L. monocytogenes in beef burgers, and the advantage of this agent sourced from mushrooms is discussed.